Bridgman growth and electrical properties of Nd-doped PMN–PT single crystal with ultrahigh piezoelectricity. Issue 4 (5th January 2022) - Chen, Ziyun; Deng, Tingyu; Chen, Rui; Lin, Di; Di, Wenning; Chen, Hongbing; Luo, Haosu; Han, Tao
Abstract : The work presents electrical properties of Nd–PMN–PT single crystal grown by Bridgman method. As-grown crystal has been verified to have ultrahigh piezoelectric coefficient d 33 with maximum value of 3650 pC N −1 under alternating current polarization. Abstract : Using the polycrystalline material with a nominal composition of Nd0.01 Pb0.985 [(Mg1/3 Nb2/3 )0.70 Ti0.30 ]O3, an Nd-doped PMN–PT single crystal has been grown successfully by a vertical Bridgman process. The perovskite structure and the crystalline phase evolution of the as-grown crystal were confirmed by X-ray diffraction analysis. A series of (001)-oriented crystal wafers, fabricated from different regions of the as-grown crystal boule, were characterized systematically to verify their electrical properties. Compared to the undoped PMN–PT single crystal, the crystal wafers under direct current polarization exhibited an improved piezoelectric coefficient d 33 of 1780–2870 pC N −1, along with a lower phase transition temperature T and a lower Curie temperature T c in the range of 55–63 °C and 95–141 °C, respectively. The coercive field E c and the remnant polarization P r for the crystal wafers were measured to be 1.7–2.7 kV cm −1 and 23.9–32.7 μC cm −2, respectively. It was found that the piezoelectric coefficient d 33 of the crystal wafer could be even elevated to the range 2200–3650 pC N −1 by applying alternating current polarization. The improved piezoelectricity for the crystal wafer under alternating current polarization may be associated with the increased domain density inside the crystal medium.